Fotografía conceptual aplicada a productos editoriales - Chicaiza Villavicencio, Germán Alejandro (2022)
This research is about conceptual photography and its impact on its adaptation to editorial producers because of the absence of knowledge of the internal and external locality of handling and applying this form of distinctive photography to know how to do it. This research study was taken under a qualitative approach. This procedure helps us collect the necessary information to propose and adapt it to a product without altering its editorial structure. The Editorial "La Prensa" has several exemplars; they handle their graphic line and compositional elements. In each of them, we try to adapt it without modifying its structure or category. To adapt conceptual photography, we have to know the kind of message that we want to transmit to the public because the image takes greater importance at the moment of transmitting a message. One of the most outstanding examples to follow is Jeff Wall, who was known as a storyteller interpreting his photographs in postmodernity. A photographer tries to bring a story, a message that can be identified with his visual audience, a message that projects an experience. The creative process of this photographic category is based on how to tell a story only by viewing its image since this way. We will continue to treat the subject of the copy. The objective is to project a new photographic application to editorial products with a new, highly functional touch in front of their copies, thus generating attractiveness.